Preparation and Properties of Waterborne Polyurethane Modified With Disperse Red 60 - Chengshu Xu; Fei Zhao; Lei OuYang; Chang An; Yan Ren (International Journal of Polymer Science)
In this study, a waterborne polyurethane (WPU) prepolymer is synthesized by using polyester 218 as the soft segment, isophorone diisocyanate (IPDI) as the hard segment, and 2,2-dimethylolpropionic acid (DMPA) as the hydrophilic chain extender. And then, the Disperse Red 60 (DR60)-WPU emulsion is obtained through a reaction between the WPU prepolymer and 1-amino-2-phenoxy-4-hydroxyanthraquinone (DR60). The properties of the structure and formed films of the DR60-WPU are then characterized by using the Fourier transform infrared spectrometry, dynamic thermomechanical analyses, and ultraviolet absorption spectroscopy, as well as by testing the water absorption. It is found that the DR60-WPU emulsion samples show excellent stability and their films show good heat resistance. When compared with the ultraviolet absorption spectrum of DR60, there is no obvious change observed in that of the DR60-WPU samples. Furthermore, the hue of DR60 can be retained in the DR60-WPU samples. And the obtained DR60-WPU has the characteristic of stable color performance. Finally, the obtained DR60-WPU samples are successfully applied as a functional finishing agent for the polyester fabric, and the resultant breaking strength, breaking elongation, and crease recovery of the treated fabric are increased in comparison to the untreated fabric. When 1.6~2.0 wt% of DR60 is added to WPU, the treated fabric can obtain a perfect finishing performance.